2007
DOI: 10.1152/jn.00581.2007
|View full text |Cite
|
Sign up to set email alerts
|

Moving From an Averaged to Specific View of Spinal Cord Pain Processing Circuits

Abstract: Graham BA, Brichta AM, Callister RJ. Moving from an averaged to specific view of spinal cord pain processing circuits. J Neurophysiol 98: [1057][1058][1059][1060][1061][1062][1063] 2007. First published June 13, 2007; doi:10.1152/jn.00581.2007. Neurons in the superficial dorsal horn (SDH) of the spinal cord play a critical role in processing potentially painful or noxious signals from skin, muscle, and viscera. Many acute pain therapies are based on the notion that altering the excitability of SDH neurons can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(83 citation statements)
references
References 74 publications
2
81
0
Order By: Relevance
“…exploring the role of genes in pain mechanisms (Graham et al 2007a;Harvey et al 2004), it is important to know when the electrophysiological properties of SDH neurons can be considered stable or "adultlike" in this species. Our data show that many electrophysiological properties change in SDH neurons during the developmental period examined (E15-P25).…”
Section: Discussionmentioning
confidence: 99%
“…exploring the role of genes in pain mechanisms (Graham et al 2007a;Harvey et al 2004), it is important to know when the electrophysiological properties of SDH neurons can be considered stable or "adultlike" in this species. Our data show that many electrophysiological properties change in SDH neurons during the developmental period examined (E15-P25).…”
Section: Discussionmentioning
confidence: 99%
“…These interneurons play a key role in the processing of nociceptive stimuli and in setting the overall "excitability level" in the spinal dorsal horn (Fields and Basbaum, 2005;Graham et al, 2007) (Fig. 3B).…”
Section: Structural Components In Nociceptive Processing Via the Spinmentioning
confidence: 99%
“…In lamina II, interneurons containing enkephalin and other neuropeptides may affect primary afferent nociceptive transmission pre-or postsynaptically. Adapted from Craig, 2003a. Approximately 30% of these neurons are inhibitory whereas the remainder is excitatory (Graham et al, 2007). These interneurons, which are preferentially located in lamina II, are under the control of powerful descending inhibitory or facilitating pathways with a supraspinal origin.…”
Section: Structural Components In Nociceptive Processing Via the Spinmentioning
confidence: 99%
“…Given the location of these superficial GABAergic interneurons, it is possible that they are associated with local afferent processing such as inhibitory transmission to substantia gelatinosa neurons (Yoshimura and Nishi, 1995). It has been shown that small inhibitory cells in the superficial dorsal horn are mostly related to processing ascending sensory information by modulating neurotransmitter release from the central terminals of primary afferents (Lao and Marvizon, 2005) and being the substrate for lateral inhibition in ascending sensory systems (Le Bars, 2002;Heinke et al, 2004;Graham et al, 2007). Heinke et al (2004) suggested that GFP-positive cells in laminae I and II in GAD67-GFP transgenic mice are involved in the transmission of nociceptive information to the brain.…”
Section: Distribution Of Gabaergic Interneurons In Gad65::gfp Micementioning
confidence: 99%